Associations between mortality and air pollution in central Europe. - Peters, A (2000)
Increased mortality has been observed in association with elevated concentrations of air pollutants in European cities and in the United States. We reassessed the effects of particulate matter in Central Europe. Mortality and air pollution data were obtained for a highly polluted region of the Czech Republic and a rural region in Germany. Poisson regression analyses were conducted considering trend, season, meteorology, and influenza epidemics as confounders in both a parametric and a nonparametric approach. The Czech Republic had a 3.8% increase in mortality [95% confidence interval (CI), 0.8-6.9%] in association with 100 microg/m(3) total suspended particles (TSP) (lagged 2 days) for the time period 1982-1994. During the last 2 years of study, 68% of the TSP consisted of particulate matter [less than/equal to] 10 microm in aerodynamic diameter (PM(10)). An increase of 100 microg/m(3) TSP (lagged 1 day) was associated with a 9.5% increase in mortality (CI, 1.2-18.5%) and 100 microg/m(3) PM(10 )(lagged 1 day) showed a 9.8% increase in mortality (CI, 0.7-19.7%). We found no evidence for an association between mortality and particulate matter in the rural area in Germany at the Czech border. Data from the coal basin in the Czech Republic suggested an increase in mortality associated with the concentration of particulate matter in a highly polluted setting in Central Europe that is consistent with the associations observed in other western European cities and in the United States.